Removal of lubricant added to iron powder metallurgy, with abnormal plasma discharge glow - Rodríguez-Fonseca, Pedro Vicente; Sarmiento-Santos, Armando; Moreno-Téllez, Carlos Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Abnormal glow discharge plasma is used in removing lubricant from iron powder metallurgical compact in a hydrogen atmosphere, in order to set the best conditions of thermal cycle in the cathodic configuration, to keep the iron characteristics offered. A rotary mixer for preparing the mixtures was used.The material was conformed with uniaxial pressure and calculating its density and porosity. With TGA and DSC, the thermal decomposition and the elimination of the lubricant is studied. The removal cycles are performed on the abnormal glow discharge plasma. With TGA the lubricant removal is monitored. Green compacts and the removal process one’s are characterized using optical and SEM microscopy.Adequate removal in the cathode configuration was achieved at 400 °C for 10 minutes. The proposed cycle should be considered for industrial applications due to high heating rates reached with reduced power consumption, and the energy required to maintain the discharge, related to the resistance furnaces used.